Small private college revitalization: a meta-study of successful college turnaround - Eaker, Rhonda Lynn Fisher, author; Gilley, Jerry, advisor (Colorado State University. Libraries, 2008)
While high profile colleges are becoming increasingly selective and garnering huge endowments, many lesser known small, private colleges are fighting for survival. A number of these colleges have experienced significant decline, but have rallied to meet the challenge and ultimately survived. Using a qualitative meta-study methodology, this research examined the revitalization process used by 45 small, private colleges. Models were developed for both the state of decline and the process of revitalization. Decline is illustrated as a cyclical process. As enrollment and finances weaken, small colleges are forced to respond in ways that continue and even exacerbate the decline resulting in a series of on-going cycles. The revitalization model demonstrates the process of breaking the cycles to reverse their momentum. It is not a linear process; instead it is a seemly haphazard mix of activities that impact finances and enrollment either directly or indirectly. Revitalization is often simply a matter of trying as many things as possible, as quickly as possible, until something works. The revitalization process was unique to each college's situation but some useful observations did emerge. For instance, a breakdown of governance responsibilities and structures seems to have a more devastating effect on a small college than it might in a larger institution. A more involved Board of Trustees and the development of widely accepted communication and decision making structures were a key part of revitalization. These academic offerings. Cutting budgets, cutting programs, or narrowing their niche were not solutions for these colleges, at least not in isolation. The study results did not necessarily advocate trying to "be all things to all people", but these colleges did need to find ways to "be more things to more people". Finally, these colleges found that increasing enrollment was a function of the entire college, not just the admissions office. The admissions function was only successful when the college took steps to enhance program offerings, upgrade facilities, improve image and develop strategic partnerships.
Keywords: change; college revitalization; college survival; college turnaround; private colleges; small colleges; school administration; higher education; private schools; colleges and universities; meta-analysis; educational administration